2012
DOI: 10.1104/pp.112.197483
|View full text |Cite
|
Sign up to set email alerts
|

Altered Chloroplast Development and Delayed Fruit Ripening Caused by Mutations in a Zinc Metalloprotease at the lutescent2 Locus of Tomato    

Abstract: The chloroplast is the site of photosynthesis in higher plants but also functions as the center of synthesis for primary and specialized metabolites including amino acids, fatty acids, starch, and diverse isoprenoids. Mutants that disrupt aspects of chloroplast function represent valuable tools for defining structural and biochemical regulation of the chloroplast and its interplay with whole-plant structure and function. The lutescent1 (l1) and l2 mutants of tomato (Solanum lycopersicum) possess a range of chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 66 publications
(74 reference statements)
2
49
0
3
Order By: Relevance
“…This is in contrast to observations with GLK2 overexpressors reported by Powell et al (2012), where no obvious effect on the timing of ripening was reported. Our results suggest that the APRR2-Like gene product may form part of a ripening signal mechanism involving the plastid compartment (Barry et al, 2012). The mechanism of action clearly demands further investigation.…”
Section: Ripening-related Gene Expression Is Altered In Tomatomentioning
confidence: 99%
“…This is in contrast to observations with GLK2 overexpressors reported by Powell et al (2012), where no obvious effect on the timing of ripening was reported. Our results suggest that the APRR2-Like gene product may form part of a ripening signal mechanism involving the plastid compartment (Barry et al, 2012). The mechanism of action clearly demands further investigation.…”
Section: Ripening-related Gene Expression Is Altered In Tomatomentioning
confidence: 99%
“…This indicates that chromoplastogenesis involves profound changes in signaling events whose details and interactions remain to be elucidated. The demonstration that chromoplasts can develop from altered chloroplasts in lutescent2 tomato fruit mutants (Barry et al, 2012) indicates that the differentiation of chromoplasts and the associated signaling events do not depend on functional chloroplasts. However, although with some delay, chromoplast formation always accompanies fruit ripening.…”
Section: Proteins Involved In Energy Provision and Translocation Actimentioning
confidence: 99%
“…Interestingly, the FtsH and EGY1 proteins decrease in abundance, mostly between the B and R stages, which correlates well with the dismantling of the thylakoid membranes, while SECA was present only at the MG stage, indicating an early end to the provision of material for thylakoid biogenesis. Recently the lutescent2 mutant of tomato has been identified as mutated for a homolog of EGY1 of Arabidopsis (Barry et al, 2012). The mutation is responsible for an altered chloroplast development and delay in fruit ripening but this not precluded chromoplast differentiation, indicating that chromoplast development does not depend on functional chromoplasts (Barry et al, 2012).…”
Section: Loss Of the Machinery For The Build Up Of Thylakoids And Phomentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that tomato L2 encodes an ortholog of Arabidopsis EGY1, which is a membrane-bound, chloroplast-targeted protease and a member of zincdependent M50 metalloprotease family, required for normal plastid development since it mediates chlorophyll accumulation (Chen et al, 2005). These evidences suggest that L2/EGY1 homologs may have a role in mediating chloroplast responses such as proteolysis of thylakoid membrane proteins during photosystem assembly or in response to environmental changes (Barry et al, 2012). Simirarly to role of Deg proteases, FtsH protease, an ATP-dependent zinc metalloprotease, play a role in light-induced turnover of D1 protein in thylakoid membranes maintaining PSII reaction centre integrity (Lindhal et al, 2000).…”
Section: Proteasesmentioning
confidence: 98%